2013
DOI: 10.5713/ajas.2013.13096
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mathematical Models Applied to F1 Dairy Sheep Lactations in Organic Farm and Environmental Factors Affecting Lactation Curve Parameter

Abstract: The objective of this study was to compare the goodness of fit of four lactation curve models: Wood’s Gamma model (WD), Wilmink (WL), and Pollott’s multiplicative two (POL2) and three parameters (POL3) and to determine the environmental factors affecting the complete lactation curve of F1 dairy sheep under organic management. A total of 5,382 weekly milk yields records from 150 ewes, under organic management were used. Residual mean square (RMS), determination coefficients (R2), and correlation (r) analysis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
2
7
1
Order By: Relevance
“…Biological parameters of the Pollott model help us to explain the characteristics of lactation, predict appropriate milk yields and detect the systematic changes in yield caused by biological factors; this is in agreement with previous work in crossbred sheep (Angeles-Hernandez et al, 2013) and pure breeds like…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Biological parameters of the Pollott model help us to explain the characteristics of lactation, predict appropriate milk yields and detect the systematic changes in yield caused by biological factors; this is in agreement with previous work in crossbred sheep (Angeles-Hernandez et al, 2013) and pure breeds like…”
Section: Discussionsupporting
confidence: 89%
“…As the lambing performance increases with age there is an improvement in the efficiency of homeorhetic dynamics involved in the partition of nutrients to the developing mammary gland and milk synthesis (González-García et al, 2015). Our results show an increase of TMY with lambing number, as previously (Angeles-Hernandez et al, 2013;González-García et al, 2015). The substantial difference of parameters that define the patterns of lactation curve and milk yield between lactation numbers are probably related to the biology of the mammary gland.. By interpreting the biological parameters from Pollott´s model, it can be established that the maximum TMY reached in third lambing is associated with lower decline in the udder cells (DR).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Several previous studies (Gootwine and Pollott 2000;Angeles-Hernandez et al 2013) reported a quadratic effect of the NL on milk production, point out that the lowest milk yields and more persistent lactation curves occur in the first lactation due to the mammary gland not being fully developed at the beginning of the first lactation (Abdelsayed et al 2015); afterwards, milk yields increase with the NL, showing the highest milk yields in the third and fourth lactation and a consequent decline until culling; this is in agreement with the results of the current study. An early study analysed the effect of the NL in milk production and BW of Chios sheep, stating higher milk yields in third lambing and maximum BWs in the fifth parity (Mavrogenis and Papachristoforou 2000); again, that coincides with our results.…”
Section: Environmental Factors That Affect Milk Productionmentioning
confidence: 99%
“…The environmental factors that affect the milk yield and lactation curve have been determined by many researchers, and different mathematical models have been proposed for determining the lactation milk yield in dairy cattle (Koncagül and Yazgan, 2011). Most of these models developed for dairy cattle can also be used to identify the lactation curves of sheep and goats (Fernandez et al, 2002;Koncagül et al, 2012;Angeles-Hernandez et al, 2013). Among them, Wood's model (1967) has been the most widely used (Nezamidoust et al, 2013;Angeles-Hernandez et al, 2013) Lactation curve studies have conducted rarely in Awassi sheep.…”
Section: Introductionmentioning
confidence: 99%